Investigating the Effects of Chelidonic Acid on Oxidative Stress-Induced Premature Cellular Senescence in Human Skin Fibroblast Cells - Turkoglu, Burcu; Mansuroglu, Banu (MDPI, 2024)
This study investigated the effects of chelidonic acid (CA) on hydrogen peroxide (H2O2) induced cellular senescence in human skin fibroblast cells (BJ). Cellular senescence is a critical mechanism that is linked to age-related diseases and chronic conditions. CA, a gamma-pyrone compound known for its broad pharmacological activity, was assessed for its potential to mitigate oxidative stress and alter senescence markers. A stress-induced premature senescence (SIPS) model was designed in BJ fibroblast cells using the oxidative stress agent H2O2. After this treatment, cells were treated with CA, and the potential effect of CA on senescence was evaluated using senescence-related beta-galactosidase, 4 ',6-diamino-2-phenylindole (DAPI), acridine-orange staining (AO), comet assay, molecular docking assays, gene expression, and protein analysis. These results demonstrate that CA effectively reduces senescence markers, including senescence-associated beta-galactosidase activity, DNA damage, lysosomal activity, and oxidative stress indicators such as malondialdehyde. Molecular docking revealed CA's potential interactions with critical proteins involved in senescence signalling pathways, suggesting mechanisms by which CA may exert its effects. Gene expression and protein analyses corroborated the observed anti-senescent effects, with CA modulating p16, p21, and pRB1 expressions and reducing oxidative stress markers. In conclusion, CA appeared to have senolytic and senomorphic potential in vitro, which could mitigate and reverse SIPS markers in BJ fibroblasts.
Keywords: chelidonic acid; senescence; senolytic; senomorphic; oxidative stress; H2O2; premature senescence; BJ Fibroblasts; NF-KAPPA-B; DNA-DAMAGE; SECRETORY PHENOTYPE; LIPID-PEROXIDATION; GENE-EXPRESSION; ASSAY; INHIBITORS; BINDING; IDENTIFICATION; STRATEGIES; Life Sciences & Biomedicine - Other Topics; Microbiology